Numerical Investigation of the Failure of Stiffened Steel Plates Subjected to Near-Field Blast Loads - Nurul Syafiqah, Abdul Razak; Aizat, Alias; Nor Maslina, Mohsan; Siti Aliyyah, Masjuki (Springer Nature, 2023)
This paper study the failure of stiffened steel plates subjected to near-filed blast loads using finite element (FE) analysis. Half-symmetry 3D FE models were developed using Abaqus for unstiffened and stiffened steel plates with different stiffeners configurations and sizes were used using solid brick elements. The behaviour of steel plates was modelled using classical plasticity constitutive equation, and the failure of the plates was modelled using ductile damage criterion. The influence of strain rates was considered using the Cowper–Symonds equation. The blast loads were applied using CONWEP function in Abaqus. The FE model of unstiffened plates was verified and validated against experimental data from literature where a good agreement was achieved. The FE model then was extended to incorporate different sizes and configurations of stiffeners. The study observed that stiffened steel plate tends to fail at lower blast pressure. The failure is influenced by the position and arrangement of stiffeners with respect to the size of stiffeners. Two new sub-modes of failure for stiffened steel plates are proposed namely Mode II*s and Mode IIs for partial plate tearing along stiffener and rupture of stiffener, respectively.